Método de utilização de membrana de celulose bacteriana intra articular sobre superfície lesada de patela - Gaspar, Ana Maria Minarelli [UNESP]; Abdalla, Cassiano de Moura; Ribeiro, Sidney José Lima [UNESP]; Saska, Sybele; Messaddeq, Younes [UNESP] (Instituto Nacional de Propriedade Industrial (INPI), 2012)
The present invention discloses the use of the bacterial cellulose membrane in ligament, tendon and synovial capsule reconstructions according to the methods described in the technical description of the invention. Said material could be used in the reconstruction of ligaments and tendons (the knee cruciate ligaments, patellar ligament, Achilles tendon, quadriceps tendon, etc.) and the synovial capsule.
Method for Using An Intra-articular Bacterial Cellulose Membrane on the Damaged Surface of a Knee Cap
Processo: WO2012167341
Número de publicação: WO2012167341 (A1)
Número de aplicação: WO2012BR00179